Organosilicon-Mediated Organic Synthesis (SiMOS): A Personal Account - Li, Li; Wei, Yun-Long; Xu, Li-Wen (Synlett, 2020)
The organosilicon-mediated organic synthesis (SiMOS) has attracted much attention over the recent decades. However, the use of organosilicon reagents with novel catalytic strategies remains to be explored. This Account summarizes our group’s progress mainly based on the application of a wide variety of organosilicon reagents, including allylic silanes, trifluoromethyl silane, acylsilanes, chlorosilanes, hydrosilanes, trimethylsilyldiazomethane, trimethylsiloxyfuran, silanols, α-trimethylsilylmethylacetate, and trimethylsilylcyanide, in catalysis and organic reactions. These transformations were proved to be alternative procedures for the construction of structurally diverse compounds.1 Introduction2 The Exploration of New Reactivity of Organosilicon Reagent in Organic Synthesis2.1 Allylic Silanes2.2 Trifluomethylsilane (TMSCF3)2.3 Acylsilanes2.4 Chlorosilanes and Hydrosilanes2.5 Trimethylsilyldiazomethane (TMSD)2.6 Trimethylsiloxyfuran2.7 Silanols2.8 Trimethylsilylcyanide (TMSCN)3 Conclusion and Perspective
Keywords: organosilicon; silanes; homogeneous catalysis; Lewis acid; silicon